مكانة الإعلام في التعامل مع تهديدات العولمة الثقافية للهوية المحلية وللأمن المجتمعي بالجزائر - بن عياش, سمير; حاج ميهوب سيدي موسى, عقيلة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تكتسي مسألة الأمن المجتمعي والهوية الثقافية إعلاميا أهمية متزايدة، تزداد هذه الأهمية من فرض وتكريس لمعالم النموذج الثقافي الغربي، في الحالة الجزائرية تطرح هذه الهيمنة توازيا مع هوية تمر بتهديدات متعددة داخلية وخارجية المصدر، فتهديدات العولمة تستدعي الاستفادة من التكنولوجيا الحديثة، كما ينبغي كذلك الاهتمام أكثر بمسائل الاندماج الاجتماعي ومخاطر توجيه الولاء المجتمعي نحو وجهات أخري بفضل استغلال ضعف الثقة ومشاكل الأمن المجتمعي المتضاعفة، فالتعامل مع الإعلام في ظل العولمة وتأثيراتها يتوجب الاستفادة من فرص الرشادة التي تتيحها،كما ينبغي المحافظة على الخصوصية المحلية دون الانطواء على النفس، ومسايرة متطلبات العصر بإيجاد حلول لجميع تهديدات الهوية الثقافية والأمن المجتمعي. Abstract: The issue of societal security and a media identity acquire an increasing importance, this importance increases to the features of the Western cultural model, in the Algerian case this domination is presented in parallel with an identity that passes multiple internal and extern al threats, The threats of globalization require taking advantage of modern technology, and redoubling efforts against what contributes to dissolving the local culture in accordance with exotic Western values, as well as more attention to social inclusion issues and the risks of directing community loyalty towards and Other, thanks to the exploitation of weak trust and the multiplying social security problems. Dealing with the media in light of globalization and its effects must take advantage of the opportunities for rationality that it provides, and must maintain local privacy without introverting one self, and keep pace with the requirements of the times by finding solutions to all threats to cultural identity and social security.